2002
DOI: 10.1530/rep.0.1240353
|View full text |Cite
|
Sign up to set email alerts
|

Caspase activity and expression of cell death genes during development of human preimplantation embryos

Abstract: It has been observed that apoptosis occurs in human blastocysts. In other types of cell, the characteristic morphological changes seen in apoptotic cells are executed by caspases, which are regulated by the BCL-2 family of proteins. This study investigated whether these components of the apoptotic cascade are present throughout human preimplantation development. Developing and arrested two pronucleate embryos at all stages were incubated with a fluorescently tagged caspase inhibitor that binds only to active c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 10 publications
5
45
1
Order By: Relevance
“…Some of the two-cell embryos which stained positive for caspases and belonged to the slow developing group may have been in developmental arrest, which is in accordance with the previous studies where apoptosis has been demonstrated in arrested two-to four-cell human and pig embryos (Spanos et al 2002, Mateusen et al 2005. Notwithstanding the presence of the full apoptotic machinery in normal developing early stage embryos, in humans, caspase could only be detected from the compacted morula stage onwards (Spanos et al 2002). A family of proteins called inhibitors of apoptosis proteins (IAPs) could play a pioneering role in this respect by binding directly to and inhibiting active caspases (Deveraux & Reed 1999, Goyal 2001, Spanos et al 2002.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Some of the two-cell embryos which stained positive for caspases and belonged to the slow developing group may have been in developmental arrest, which is in accordance with the previous studies where apoptosis has been demonstrated in arrested two-to four-cell human and pig embryos (Spanos et al 2002, Mateusen et al 2005. Notwithstanding the presence of the full apoptotic machinery in normal developing early stage embryos, in humans, caspase could only be detected from the compacted morula stage onwards (Spanos et al 2002). A family of proteins called inhibitors of apoptosis proteins (IAPs) could play a pioneering role in this respect by binding directly to and inhibiting active caspases (Deveraux & Reed 1999, Goyal 2001, Spanos et al 2002.…”
Section: Discussionsupporting
confidence: 91%
“…The fluorescent detection of active caspases as early as the two-cell stage in our study has confirmed this possibility. Some of the two-cell embryos which stained positive for caspases and belonged to the slow developing group may have been in developmental arrest, which is in accordance with the previous studies where apoptosis has been demonstrated in arrested two-to four-cell human and pig embryos (Spanos et al 2002, Mateusen et al 2005. Notwithstanding the presence of the full apoptotic machinery in normal developing early stage embryos, in humans, caspase could only be detected from the compacted morula stage onwards (Spanos et al 2002).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although little is known about possible signals that may trigger apoptosis in embryos and the precise mechanisms by which the apoptosis program is executed and controlled, all apoptotic pathways appear to terminate with activation of the caspase family of proteases [10][11][12]. The caspase family of cysteine proteases mediates proteolytic cleavage of a large number of proteins important for cell integrity and survival and finally activates the endonucleases that are responsible for DNA fragmentation [13][14][15].…”
mentioning
confidence: 99%